Gender ratio trends over time in multiple sclerosis patients from Argentina. (April 2017) - Rojas, J.I.; Patrucco, L.; MIguez, J.; Sinay, V.; Cassara, F. Pagani; Cáceres, F.; Liguori, N. Fernandez; Saladino, M.L.; Deri, N.; Jaacks, G.; Marcilla, M. Parada; Arrigoni, M.I.; et al.
Highlights: A disproportional increase of multiple sclerosis in women were reported in the last years. This multicenter study that included patients from 14 MS Centers of Argentina. The study assessed the gender ratio trends over a 50-year span in MS populations. 1069 patients were included. Gender ratios showed an increase from the first to the last decade (1.8 to 2.7; p value = 0.023). The study showed a modest increase of the F/M ratio (from 1.8 to 2.7) among patients affected. Abstract: Several studies in multiple sclerosis (MS) suggest a trend of increasing disease frequency in women during the last decades. A direct comparison of gender ratio trends among MS populations from Argentina remains to be carried out. The objective of the study was to compare gender ratio trends, over a 50-year span in MS populations from Argentina. Methods: multicenter study that included patients from 14 MS Centers of Argentina. Patients with definite MS with birth years ranging from 1940 to 1989 were included. Gender ratios were calculated by five decades based on year of birth and were adjusted for the F/M born-alive ratio derived from the Argentinean national registry of births. The F/M ratios were calculated using a multivariate logistic regression per five decades by the year of birth approach. Analyses were performed using Stata 10.1. Results: 1069 patients were included. Gender ratios showed a significant increase from the first to the last decade in the whole MS sample (from 1.8 to 2.7; p value for trend = 0.023). The Gender ratio did not show differences considering MS subtype. Conclusion: our study showed a modest increase of the F/M ratio (from 1.8 to 2.7) over time among patients affected by MS in Argentina.